Laboratory Simulative Clogging Behaviour And Fracture Toughness Of One And Two-Layer Porous Asphalt - Abdullah, Noor Halizah (2012)
Clogging causes porous asphalt to lose its permeability function after a few years in service. Therefore, two-layer porous asphalt was developed to minimize this problem. This study presents a laboratory simulative test of clogging phenomenon occurred on porous pavements. To ascertain the clogging of porous asphalt, one and two-layer specimens were subjected to six clogging and cleansing cycles. The permeability loss was assessed using a falling head water permeameter. Porous asphalt specimens were tested incorporating conventional 60/70 and PG76 modified bitumen at four binder contents and three different top layer thicknesses of two-layer specimens. Selected specimens were subjected to temperature conditioning (10, 30 and 50 °C) to determine the effects of temperature to the severity of clogging. Semicircular bending test was used to assess the fracture toughness of porous asphalt. One and two-layer specimens were tested at 0, 10 and 20 °C testing temperatures. The overall results showed that porous asphalt loses its permeability mainly in the first two to three clogging and cleansing cycles. The clogging trend exhibits an exponential pattern with addition of clogging material. The performance of porous asphalt in resisting clogging can be ranked from the clogging and clog-recovery index. It was also found that two-layer specimens were a better clog-resistant mix compared to one-layer specimens while top layer thicknesses of two-layer specimen have no significant effect on clogging. Binder type and content have significant effects on clogging of porous asphalt. Higher temperature caused severe clogging to the mix and lower temperature result in least clogged mix. Generally, lower testing temperature resulted in higher fracture toughness. Subsequently, one-layer specimen exhibit higher fracture toughness compared to two-layer specimen and binder types also exhibit significant effect on the fracture toughness of porous asphalt.